Beauty and virtue. The message of the postcards and representations of women in cities in the pampas of argentina at the beginning of the 20th century. (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
This paper deals about the quick changes in the constitution of a familiar pattern and other topics of female sexual moral, between the late nineteenth and early twentieth centuries. It attempts to identify the mechanisms that led women to adopt a more rigid sexual moral, with stereotyped forms of generic relations and a passive,  subordinated role of women. Through a "great man" of  Pampas, as a "guardian" of the local young women -as showed in the thirty-four letters written between August 1903 and september 1904- we analyzed the relationships among the “honourable residents" of the community, and the moral principles exalted  in the speech.
Keywords: Woman; family; virtue; moral; Buenos Aires cities.